Sozialgruppen als Forschungsgegenstand der Geographie: Gedanken zur Systematik der Anthropogeographie - Hahn, Helmut (ERDKUNDE, 1957)
German geography has recognised only relatively late the bearing that social groups have on the shaping of the cultural landscape. During the last few decades, however, a good deal of preliminary work has been done, and it seems that the time has now come to give social geography its logical place within the field of geography as a subject in teaching and research. A brief review of the development of human geography since Ratzel and an analysis of the content and task of social geography shows that it is by no means identical with human geography as is claimed here and there in more recent publications. Like all geographical research social geography must be pursed analytically and synthetically. Since man shapes the cultural landscape almost exclusively merely as a member of a group, as a social being, synthetic human geography can, however, only be pursued in the form of social geography. The established branches of analytical human geography, i. e. population, settlement, economic and commercial geography, geography of communications and in particular physical and psychical anthropogeography (as understood by Ratzel) completely retain the justification of their existence beside the analytical social geography. (In order to make the distinction clearer it should rather be called socio-geography.) The different manifestations of human activity are materially so closely tied to the laws of the inorganic and biological spheres, that we should not cut ourselves off from the possibility of a penetrating analysis by a onesided emphasis of the social sphere. Social geography merely aims to juxtapose to the causally determined complex of physical nature a cultural spatial complex shaped by human forces and thus to facilitate deeper penetration into the interrelationship existing within the cultural landscape (habitat and human society)